Posterolateral Versus Transforaminal Interbody L4/5 Fusion: Correlation With Subsequent Surgery. Issue 2 (March 2019) - Gaffney, Christian J.; Pinto, Manuel R.; Buyuk, Abdul F.; Garvey, Timothy A.; Mueller, Benjamin; Schwender, James D.; Transfeldt, Ensor E.; Tam, Harrison K.; Dawson, John M.
Abstract : Study Design: This is a retrospective cohort study. Objective: To compare posterolateral versus transforaminal interbody fusion (PLF vs. PLF+TLIF) of the L4/5 segment regarding rates of subsequent surgery, clinical and radiographic parameters, and patient satisfaction. Summary of Background Data: Surgical treatment of lumbar stenosis, decompression with or without fusion, is an efficacious treatment in select patients. Reoperation is thought to be a problem after lumbar fusion. Despite multiple studies, the fusion method that minimizes the need for subsequent surgery has yet to be determined. Materials and Methods: A retrospective cohort study was conducted on 89 patients who had an isolated L4/5 decompression and fusion, from January 2006 to 2012. All patients had stenosis and degenerative spondylolisthesis at the L4/5 level. All surgeries were performed at a single center, using either PLF (31 patients) or PLF+TLIF (58 patients) techniques. Preoperative and postoperative patient-reported outcome measures (Oswestry disability index, visual analog scale back pain, visual analog scale leg pain) and radiographic parameters (L4/5 lordosis and overall lumbar lordosis) were measured. Patient satisfaction was acquired via a questionnaire. Chart reviews and patient questionnaires were used to determine the incidence of subsequent lumbar surgery over a minimum follow-up of 5 years. Results: At an average of 8.7 years follow-up, 2 of 31 patients in the PLF group had subsequent lumbar surgery, compared with 16 of 58 patients in the PLF+TLIF group (6% vs. 28%; P =0.02). There were no significant differences between groups with respect to sex, age, body mass index, tobacco, perioperative measures, patient-reported outcomes, or radiographic parameters ( P >0.05). Conclusions: Both PLF and PLF+TLIF are effective fusion methods for L4/5 stenosis and spondylolisthesis. In this study, patients treated with PLF were less likely to undergo a subsequent lumbar surgery. More research is needed to determine which factors influence whether PLF or PLF+TLIF should be used in these patients. Level of Evidence: Level III.